An In-Vitro Evaluation of Turbulence after Transcatheter Aortic Valve Implantation - Hatoum, Hoda (J Thorac Cardiovasc Surg, 2018)
OBJECTIVE: This study aims at assessing post-transcatheter aortic valve(TAV) replacement hemodynamics and turbulence where a same-size SAPIEN3 and Medtronic Evolut are implanted in a rigid aortic root with physiological dimensions and in a representative root with calcific leaflets obtained from patient CT scans. METHODS: TAV hemodynamics were studied by placing a SAPIEN3 26mm and an Evolut 26mm in rigid aortic roots and representative root with calcific leaflets under physiological conditions. Hemodynamics were assessed using high-fidelity particle-image-velocimetry and high-speed imaging. Transvalvular pressure gradients (PG), pin-wheeling indices (PI) and Reynolds shear stress(RSS) were calculated. RESULTS: (a) PGs obtained with the Evolut and the SAPIEN3 were comparable among the different models (10.5±0.15mmHg vs. 7.76±0.083mmHg in the rigid model along with 13.9±0.19mmHg vs. 5.0±0.09mmHg in representative root with calcific leaflets obtained from patient CT scans respectively); (b) more pinwheeling was found in the SAPIEN3 than the Evolut (0.231±0.057 vs. 0.201±0.05 in the representative root with calcific leaflets and 0.366±0.067 vs. 0.122±0.045 in the rigid model), (c) Higher RSS were found in the Evolut (161.27±3.45 vs. 122.84±1.76Pa in representative root with calcific leaflets and 337.22±7.05 vs. 157.91±1.80Pa in rigid models). More lateral fluctuations were found in representative root with calcific leaflets. CONCLUSION: (a) Comparable PGs were found among the TAVs in different models (b) PIs were found different between both TAVs; (b) Turbulence patterns among both TAVs translated by RSS were different. Rigid aortic models yield more conservative estimates of turbulence; (c) Both TAVs exhibit peak maximal RSS that exceeds platelet activation 100Pa threshold limit.